The relationship between the feather tuft of the uropygial gland and terrestrial/aquatic birds - Chiale, Maria Cecilia (2013)
The bird´s uropygial gland has a papilla in its caudal end and it can also show a feather tuft. These feathers may have a raquis or not. The purpose of our study was to compare the number, dimensions and types of the tuft´s feathers in aquatic and terrestrial birds, as well as to investigate whether the potential differences are related or determined by their dissimilar habitats. The uropygial glands were removed and the tuft´s feathers were extracted and then measured, prepared for magnifying glass observation and photo shoot. Aquatic birds were found to have not only a larger number of feathers in the tuft but also longer feathers than terrestrial birds. However, the length ratio between calamus/raquis was higher in terrestrial birds. Almost all the species under study presented the same type of feathers except for the three penguin species that showed a peculiar type. The differences found between the tuft´s feathers of the studied species are related with the environment. Aquatic birds have a longer length of the feather tuft because they may produce a greater amount of secretion than terrestrial birds.